Management of Coincident Pituitary Macroadenoma and Cavernous Carotid Aneurysm: A Systematic Literature Review - Piper, Keenan J.; Karsy, Michael; Barton, Blair; Rabinowitz, Mindy; Rosen, Marc R.; Nyquist, Gurston G.; Evans, James J.; Tjoumakaris, Stavropoula; Farrell, Christopher J. (Journal of Neurological Surgery Reports, 2021)
Introduction Pituitary adenomas are a common intracranial pathology with an incidence of 15 to 20% in the population while cerebral aneurysms are less common with a prevalence of 1:50 patients. The incidence of aneurysms in patients with pituitary adenoma has been estimated at 2.3 to 5.4% of patients; however, this remains unclear. Equally, the management of concomitant lesions lacks significant understanding.Methods A case report is presented of a concomitant cerebral aneurysm and pituitary adenoma managed by minimally invasive endovascular and endoscopic methods, respectively. A systematic review of the literature for terms “pituitary adenoma” and “aneurysm” yielded 494 studies that were narrowed to 19 relevant articles.Results We report a case of a 67-year-old patient with an enlarging pituitary macroadenoma, cavernous carotid aneurysm, and unilateral carotid occlusion. After successful treatment of the aneurysm by a pipeline flow diverter, the pituitary adenoma was surgically resected by an endoscopic transsphenoidal approach.Conclusion The use of a pipeline flow diverter and endonasal approach was feasible in the treatment of our patient. This is the first report to our knowledge of the use of pipeline flow diversion in the management of a cavernous carotid aneurysm prior to pituitary adenoma treatment.
Keywords: macroadenoma; cavernous carotid aneurysm; pipeline; endoscopic; transphenoidal; pituitary adenoma; intracranial aneurysm